2006
DOI: 10.1186/1471-2253-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Neuroaxial anesthesia in a patient with progressive systemic sclerosis : case presentation and review of the literature on systemic sclerosis

Abstract: BackgroundSystemic sclerosis (SSc), a progressive disease characterized by excessive accumulation of connective tissue components. Although most patients have long survival, some of them progress rapidly to death. Pulmonary system involvement and pulmonary hypertension are the most frequent cause of death. When the patient with SSc is to be operated, the anesthetic procedure could be a serious problem. In this article, we report a combined spinal – epidural technique in a patient with progressive SSc and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…It should be kept in mind that owing to decreased circulation and fibrosis of tissue, the duration of action of local anesthetic may be prolonged. Review of literature has revealed that a smaller dose of local anesthesia is required [26] .…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that owing to decreased circulation and fibrosis of tissue, the duration of action of local anesthetic may be prolonged. Review of literature has revealed that a smaller dose of local anesthesia is required [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Regional anesthesia may be limited, however, by technical difficulties, prolonged sensory blockade, unpredictable spread of local anesthetics,27,47,49,50 and associated with marked cardiovascular compromise 27…”
Section: The Use Of Regional Anesthesia In Systemic Sclerosismentioning
confidence: 99%
“…The six more recent case reports of neuroaxial anesthesia in patients with SSc do not report prolongation of block. Agents used were bupivacaine, ropivacaine, and prilocaine 27,49,50,5557…”
Section: The Use Of Regional Anesthesia In Systemic Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several local anesthetic techniques have been used in treating CeH, including occipital nerve blocks, cervical facet joint blocks, and cervical epidural injections [ 8 – 11 ]. Real time fluoroscopy imaging guidance is frequently required to ensure correct needle placement [ 12 – 14 ]. However, repeated exposure to radiation is a great threat to the health of physicians.…”
Section: Introductionmentioning
confidence: 99%